2014
DOI: 10.5935/medicalexpress.2014.05.12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacology of dobutamine and dopamine in preterm neonates

Abstract: Dobutamine is a b 1 selective stimulant. b Receptor agonists are used to stimulate the rate and the force of cardiac contraction. The chronotropic effect is useful for the treatment of arrhythmias whereas the inotropic effect is useful to augment the myocardial contractility. Dobutamine is about four times as potent as dopamine in stimulating myocardial contractility in low concentrations and increases left ventricular output in the hypotensive preterm infants. Dobutamine possesses a center of asymmetry. The (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…The delayed response to dobutamine and need to use higher doses of atropine may be related to effect of metabolites in ESRD that may blunt the heart response to dobutamine as dobutamine is metabolized by the liver and no role of kidney in dobutamine metabolism. Although previous report in pediatrics of delayed clearance of dobutamine in infants with serum creatinine concentrations >2 mg/dl [20]. This observation alerts the alternative protocol of accelerated DSE [21] where atropine is used at dobutamine dose of 20 µ/kg/min that could decrease the procedure time and dose of dobutamine used.…”
Section: Discussionmentioning
confidence: 65%
“…The delayed response to dobutamine and need to use higher doses of atropine may be related to effect of metabolites in ESRD that may blunt the heart response to dobutamine as dobutamine is metabolized by the liver and no role of kidney in dobutamine metabolism. Although previous report in pediatrics of delayed clearance of dobutamine in infants with serum creatinine concentrations >2 mg/dl [20]. This observation alerts the alternative protocol of accelerated DSE [21] where atropine is used at dobutamine dose of 20 µ/kg/min that could decrease the procedure time and dose of dobutamine used.…”
Section: Discussionmentioning
confidence: 65%
“…If whole-body circulation does not improve despite the use of drugs, it may be necessary to continue the use of vasoconstrictors and inotropic agents in large quantities. However, the continuing application of vasoconstrictors and inotropic agents in large doses may cause hypodermic tissue ischemia and peripheral vasoconstriction, and ultimately, tissue necrosis [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…[ 215 , 216 , 217 , 218 , 219 ]. Besides these functions of DA on brain functions, Pacifici [ 220 ] reported that DA could be used to increase blood pressure and urine output as well as for pediatric treatments [ 221 ]. The sourcing of DA is potentially important to the drug industry.…”
Section: Marine-based Beneficial Moleculesmentioning
confidence: 99%